2011
DOI: 10.1242/jeb.059923
|View full text |Cite
|
Sign up to set email alerts
|

Increased plant volatile production affects oviposition, but not larval development, in the moth Helicoverpa armigera

Abstract: SUMMARYIt is well established that herbivorous insects respond to changes in plant odour production, but little attention has been given to whether these responses relate to direct fitness costs of plant volatile production on insect growth and survival. Here, we use transgenic Nicotiana tabacum (tobacco) plants that produce relatively large amounts of the volatile (S)-linalool to study whether the responses of egg-laying herbivorous insects to linalool production relate directly to the growth and survival of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
41
1
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 54 publications
(43 citation statements)
references
References 47 publications
0
41
1
1
Order By: Relevance
“…Genetic manipulation of plants for terpenoid emission is a promising method to alter tritrophic interactions. In recent years, transgenic plants producing terpenoids have been used to repel herbivores (Aharoni et al, 2003), deter oviposition (McCallum et al, 2011) and attract predators (Bouwmeester et al, 2003;Kappers et al, 2005;Beale et al, 2006) and parasitoids (Schnee et al, 2006). The physiological cost of terpenoid production has been assumed to be minor, given their low molecular weight and the relatively low concentrations emitted (Dicke and Sabelis, 1990;Halitschke et al, 2000).…”
Section: Conclusion and Future Prospectsmentioning
confidence: 99%
“…Genetic manipulation of plants for terpenoid emission is a promising method to alter tritrophic interactions. In recent years, transgenic plants producing terpenoids have been used to repel herbivores (Aharoni et al, 2003), deter oviposition (McCallum et al, 2011) and attract predators (Bouwmeester et al, 2003;Kappers et al, 2005;Beale et al, 2006) and parasitoids (Schnee et al, 2006). The physiological cost of terpenoid production has been assumed to be minor, given their low molecular weight and the relatively low concentrations emitted (Dicke and Sabelis, 1990;Halitschke et al, 2000).…”
Section: Conclusion and Future Prospectsmentioning
confidence: 99%
“…However, constitutive or induced/engineered linalool emission can also serve in plant defense (Junker et al, 2011;McCallum et al, 2011;Xiao et al, 2012), and linalool can also attract antagonistic flower visitors such as thrips (Koschier et al, 2000). In addition, herbivoreinduced emission of linalool has been found to affect multitrophic interactions in several systems, where it attracts herbivores as well as their predators and parasitoids Turlings et al, 1995;Xiao et al, 2012).…”
Section: Cyp76c1 Influences the Interactions Of Flowers With Insectsmentioning
confidence: 99%
“…More recently, ref. 30 reported contradictory data, and showed that increased emission of (+)-Linalool from transgenic tobacco plants deters oviposition by the moth Helicoverpa armigera, but has no effect on larval development or feeding. 30 Since we did not investigate the chirality of linalool identified in our experiments it is not possible to predict the likely effect of increased emission upon insect behavior.…”
Section: Resultsmentioning
confidence: 99%